PENINGKATAN MINAT BACA GENERASI SEKOLAH MELALUI PENDIRIAN PERPUSTAKAAN ALAM KANAL SUKO-SUKO DI DESA SUKOREJO - Aprillianto, Bayu; Marshelina, Riska; Qomaria, Firzanah Yahya; Kholidah, Amilatul; Ilannajah, Annufus; Musi, Mardiajeng Pawestri; Wulandari, Novi; Purnamawati, Indah (Abdi Panca Marga, 2024)
Sukorejo Village is one of the villages in Jember Regency, where the reading interest among school-aged children remains low. Reflecting the common challenges faced by the younger generation today, Sukorejo Village requires concrete efforts to foster a reading culture, enabling the youth to perceive books as gateways to the world, thereby enhancing their knowledge and insights. Sukorejo Village features a tourist attraction known as the "Suko-Suko Canal," a serene destination with stunning natural landscapes along the river, surrounded by local small and medium-sized enterprises (SMEs). This community engagement initiative aims to explore the development of a nature-based library at the Suko-Suko Canal as a means of promoting reading interest among the younger generation. The method employed involves conducting a Focus Group Discussion (FGD) to design the concept and management of the nature-based library, followed by its establishment and culminating in a formal launch event. The outcomes of the initiative reveal that the library was designed and established to harmonize with the surrounding environment, featuring a collection of books focusing on environmental literacy, local culture, and children's education. During the socialization phase, various literacy activities, such as group reading sessions and educational games, successfully increased student participation and reading interest. The establishment of this nature-based library not only promotes literacy but also supports environmental conservation, offering an innovative solution to improve the literacy culture in Indonesia. Through an educational-recreational approach, the Suko-Suko Canal nature-based library has the potential to serve as a model for literacy development integrated with tourism in other regions. Keywords: Educational Tourism, Environmental literacy, Nature library, Reading Interest, Suko-Suko Canal Tourism